UPSKILL MATH PLUS

Learn Mathematics through our AI based learning portal with the support of our Academic Experts!

Learn moreLet us see the procedure to solve the quadratic equation by completing the square.

**Step 1**: Write the given equation in standard form \(ax^2 + bx + c = 0\).

**Step 2**: Make sure the coefficient of \(x^2\) is \(a = 1\). If not, make it by dividing the equation by \(a\).

**Step 3**: Move the constant term to the right-hand side of the equation.

**Step 4**: Add the square of one-half of the coefficient of \(x\) to both sides. [That is, add \(\left(\frac{b}{2}\right)^2\).]

**Step 5**: Make the equation a complete square and simplify the right-hand side.

**Step 6**: Solve for \(x\) by taking the square root on both sides.

Example:

**Find the root of**\(2x^2 + 7x - 15 = 0\)

**by the method of completing the square**.

**Solution**:

The given equation is \(2x^2 + 7x - 15 = 0\).

Here, the coefficient of \(x^2\) is \(2\). So, divide the equation by \(2\).

$\frac{2}{2}{x}^{2}+\frac{7}{2}x-\frac{15}{2}=\frac{0}{2}$

${x}^{2}+\frac{7}{2}x-\frac{15}{2}=0$

Move the constant term to the right hand side of the equation.

${x}^{2}+\frac{7}{2}x=\frac{15}{2}$

Add the square of one half of the coefficient of \(x\) to both sides.

${x}^{2}+\frac{7}{2}x+{\left(\frac{7}{4}\right)}^{2}=\frac{15}{2}+{\left(\frac{7}{4}\right)}^{2}$

${x}^{2}+2\times \frac{7}{4}x+{\left(\frac{7}{4}\right)}^{2}=\frac{15}{2}+\frac{49}{16}$

Left hand side equation reminds the identity \((a + b)^2 = a^2 + 2ab + b^2\).

${\left(x+\frac{7}{4}\right)}^{2}=\frac{120+49}{16}$

${\left(x+\frac{7}{4}\right)}^{2}=\frac{169}{16}$

Taking square root on both sides.

$x+\frac{7}{4}=\pm \frac{13}{4}$

$x=\frac{13}{4}-\frac{7}{4}$ or $x=-\frac{13}{4}-\frac{7}{4}$

$x=\frac{6}{4}$ or $x=\frac{-20}{4}$

\(x =\) $\frac{3}{2}$ or \(x = -5\)

Therefore, the roots of the given equation are $\frac{3}{2}$ and \(-5\).

**2**.

**Find the roots of the equation**\(x^2 + x + 2 = 0\)

**by completing the square method**.

**Solution**:

The given equation is \(x^2 + x + 2 = 0\)

Here, the coefficient of \(x^2\) is \(1\).

\(x^2 + x + 2 = 0\)

Move the constant term to the right hand side of the equation.

\(x^2 + x = -2\)

Add the square of one half of the coefficient of \(x\) to both sides.

${x}^{2}+x+{\left(\frac{1}{2}\right)}^{2}=-2+{\left(\frac{1}{2}\right)}^{2}$

${x}^{2}+2\times \frac{1}{2}x+{\left(\frac{1}{2}\right)}^{2}=-2+\frac{1}{4}$

${\left(x+\frac{1}{2}\right)}^{2}=-\frac{7}{4}$ \(< 0\)

The above equation cannot be possible because the square of any number cannot be negative.

**Therefore, the given equation has no real roots**.